Long‐term changes in layered soil temperature based on ground measurements in Jiangsu Province, China. (19th January 2021) - Shi, Xiao; Wang, Guojie; Chen, Tiexi; Li, Shijie; Lu, Jiao; Hagan, Daniel Fiifi T.
Abstract: While air temperature has been widely investigated to better understand the recent climate changes, the importance of soil temperature has been underestimated and rarely studied. Here, the long‐term soil temperature changes and the occurrence of extreme heats have been studied based on daily measurements in Jiangsu Province for 1970–2017. A general warming trend in soil temperature is observed at most stations, and these trends are more pronounced in the cold seasons than the warm seasons. Due to the asymmetric warming of maximum and minimum soil temperatures over the past 48 years, the diurnal range shows a long‐term decreasing trend with a rate of −0.34°C/10a. The occurrences of extreme soil temperatures have been analysed based on the probability density functions. It is found that the hot soil days have increased and cold soil days have decreased significantly, and these changes are particularly significant in the most recent decades. Abstract : Climate warming leads to soil temperature changes, as well as extreme heats. Significant warming trends of soil temperature are observed at different soil depths from daily measurements of 36 years in Jiangsu province, China. The increase of extreme heats is particularly significant in the most recent 10 years.